Distribution and diet of wintering Tundra Bean Geese Anser fabalis serrirostris at Shengjin Lake, Yangtze River floodplain, China - Zhai, Mei Juan; Cao, Lei; Fox, Anthony D (Wildfowl, 2013)
More than half of the estimated global flyway population of Tundra Bean Geese Anser fabalis serrirostris was counted at the Shengjin Lake National Nature Reserve, Anhui Province, China, in winter 2008/2009, peaking at 41,500 birds in mid-December 2008. In October–November and March, when fewer geese were recorded, the birds were found on sedge Carex meadows, because high water levels restricted access to other food resources at this time. Much larger numbers coincided with lowest water levels in mid-winter, when faecal analysis showed that geese fed on a wide range of additional food items. These included the grass Alopecurus aequalis, submerged Water Chestnut Trapa maximowiczii fruits exposed by falling water levels, and fields of winter wheat. The extent of floating Water Chestnut in summer has more than doubled from 4.2 to 9.1 km2 at Shengjin Lake since 2002 (potentially linked to eutrophication at the site), but more study is required to support the hypothesis that this source of winter food is responsible for dramatic recent increases in Bean Goose numbers at the site.